KONSTRUKSI NORMA HUKUM KOPERASI SYARIAH DALAM KERANGKA SISTEM HUKUM KOPERASI NASIONAL - Triana Sofiana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This issue comes from the Syariah Cooperation, which relies on the various legislation rule. It is only in the level of the Minister Regulation and Policy, that raises uncertainty in law practice that influences the empowering syariah cooperation departments. Therefore, the constructing of Syariah Cooperation Laws is important for planning National Cooperation Law. Actually, constructing Syariah Cooperation Law can be conducted using some approaches, such as: formal and materialistic islamic approach. It means that Islamic law can be National Law Regulation materially and formally. Second, law material approach. In taqnin process, Islamic law can be implemented as the sources of the material of law, that the principals are appropriate with the product of regulation and lgislation. Third, persuasive and authority source approach. Formally and materially, Islamic law is transformed through persuasive and authority source. Those three approaches must be used integrally and become a system in the planning of National cooperation law, in order to realize legal and prosperous society.